Dramaturgia elástica de Millôr Fernandes - Alice Carvalho Diniz Leite (2023)
This thesis focuses on investigating Dramaturgia Elástica de Millôr Fernandes [Millôr Fernandes’ Elastic Theater]; an amalgamation of eighteen plays penned by Fernandes between the 1950s and 1990s. My analysis observes and discusses how A necessidade torna o raciocínio elástico [Reasoning becomes elastic through necessity] inside the Brazilian playwright’s work. First, I propose a panoramic study of the main theatrical devices present in the plays A Woman in Three Acts [1954], The Deceased’s Measures [1955], As Graceful as a God [1955], Pigmaleoa [1955], The Seagull [1959], An Elephant in the Chaos [1960], Freedom, Freedom [1965], Vidigal [1966], The Undying Widow [1967], Man from Head to Toe [1967], Compute, Computer, Compute [1972], History is a Story [1976], It is… [1977], What a Heck of a Time, huh!? [1979], Janio’s Orphans [1980], Two Clapboards and One Love [1982], Flávia, Head, Trunk and Members [1985] e Kaos [1995]. Secondly, this thesis juxtaposes some general reflections on dramaturgy by Brazilian critics in contrast to distinct criticism on Fernandes’ style. Thirdly, this thesis inspects specific interactions among some characters in order to evince the possible meanings for the following concepts: a necessidade [necessity], torna [becoming], o raciocínio [reasoning] e elástico [elastic]. To conclude, this thesis fastidiously identifies the formal features that belong to the eighteen aforementioned plays and, from nuances intertwined to time, space, and the literary genres, emphasizes four main structural aspects: conventional drama composition; narrative scene; lyrically-epically mediated plots; and elastic performance.